ANALISIS UMUR REPRODUKSI PALING AWAL DAN PALING AKHIR SERTA PUNCAK FERTILITAS PADA WANITA DI SETIAP KABUPATEN DAN KOTA DI PROVINSI BANTEN - Rani Septiani Sukandar; Lukmanul Hakim; Miftahul Huda (LPPM Universitas Bina Bangsa, 2023)
The birth rate (fertility) is one of the factors that influences the increase in population. Banten Province has 8 districts and cities with different fertility rates. One of the fertility indicators presented in the Long Form SP2020 data is Birth Rate data by Age Group / Age Specific Fertility Rate (ASFR). The aim of this research is to determine the earliest, latest reproductive age and the age of women who have the highest fertility rates in each district and city in Banten Province. The skewness (measure of slope) and kurtosis (measure of sharpness) values of the continuous curve formed will also be studied. ASFR data presented by the Central Statistics Agency (BPS) is discrete data. Fertility rates will be approached using the MBF (Modified Beta Function) continuous fertility model. In this research, information was obtained that the earliest reproductive age in Banten Province was 15.64 years. This happened to women in Lebak Regency. Meanwhile, the latest reproductive age in Banten Province is 49.85 years. This happened to women in Pandeglang Regency. It can also be seen that the highest peak fertility rate for the population of Banten Province occurred in women aged 27.54 years in the Cilegon City area, with a peak fertility value of 0.13055. Apart from being based on calculations, this is in accordance with the curve visualization carried out using Mathematica software. The highest skewness value occurs in the continuous fertility curve for the Lebak Regency area. This means that Lebak Regency has the most left-leaning curve. All continuous fertility curves in districts and cities in Banten Province have a platykurtic distribution (flat curve) because the kurtosis value is smaller than 0.263